USE OF DIGITAL TECHNOLOGIES IN THE EDUCATIONAL PROCESS: Sagdullaev Pulatbek, Gulmira Mirzaeva - Sagdullaev Pulatbek, Acting Associate professor of Tashkent State pedagogical University; Gulmira Mirzaeva, Teacher, Tashkent State Pedagogical University (Лучшие интеллектуальные исследования, 2024)
This scientific article explores the use of digital technologies in the educational process and its effects on teaching and learning. Through a literature review and analysis of empirical data, the study examines the advantages, challenges, and outcomes associated with integrating digital technologies in education. Findings indicate that digital technologies enhance student engagement, provide access to resources, foster collaboration, and improve academic performance. Recommendations are provided for educators and policymakers to effectively incorporate digital technologies in education, promoting its potential for transformative learning experiences